Strength building in student weightlifters - Shafikova, L. R.; Greb, A. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of the experimental strength building model tested on the student weightlifters at Ufa State Petroleum Technological University (USPTU) by a 5-month-long (October 2016 to March 2107) educational experiment in the regular (90 minutes 3 times a week) training sessions. Subject to the experiment were 17-18 year-old first-year students (n=26) split up into Experimental Group (EG) and Reference Group (RG) of 13 people each. The RG was trained as required by the standard training program; and in the EG trainings the focus was on the competitive strength-building practices with the special strength and general strength components expanded to 70% and 30% of the training time, respectively. Back squats, clean and jerk and bench press exercises were dominating in these practices and tests. The two-stage (October and March) progress tests showed a significant progress of the EG versus RG as verified by the group average test rates in every test (p<0.01-0.001); with the RG progress found less expressed in the statistical terms (p<0.05). The pre-experimental strength rates were tested virtually the same in both of the groups as verified by the insignificant (p>0.05) intergroup differences in the pre-experimental test rates.